Inositol Phosphoryl Transferase, Ipt1, Is a Critical Determinant of Azole Resistance and Virulence Phenotypes in Candida glabrata - Garima Shahi; Mohit Kumar; Nitesh Kumar Khandelwal; Atanu Banerjee; Parijat Sarkar; Sonam Kumari; Brooke D. Esquivel; Neeraj Chauhan; Amitabha Chattopadhyay; Theodore C. White; Naseem A. Gaur; Ashutosh Singh; et al. (Journal of Fungi, 2022)
In this study, we have specifically blocked a key step of sphingolipid (SL) biosynthesis in Candida glabrata by disruption of the orthologs of ScIpt1 and ScSkn1. Based on their close homology with S. cerevisiae counterparts, the proteins are predicted to catalyze the addition of a phosphorylinositol group onto mannosyl inositolphosphoryl ceramide (MIPC) to form mannosyl diinositolphosphoryl ceramide (M(IP)2C), which accounts for the majority of complex SL structures in S. cerevisiae membranes. High throughput lipidome analysis confirmed the accumulation of MIPC structures in ΔCgipt1 and ΔCgskn1 cells, albeit to lesser extent in the latter. Noticeably, ΔCgipt1 cells showed an increased susceptibility to azoles; however, ΔCgskn1 cells showed no significant changes in the drug susceptibility profiles. Interestingly, the azole susceptible phenotype of ΔCgipt1 cells seems to be independent of the ergosterol content. ΔCgipt1 cells displayed altered lipid homeostasis, increased membrane fluidity as well as high diffusion of radiolabeled fluconazole (3H-FLC), which could together influence the azole susceptibility of C. glabrata. Furthermore, in vivo experiments also confirmed compromised virulence of the ΔCgipt1 strain. Contrarily, specific functions of CgSkn1 remain unclear.